UPAYA MENINGKATKAN KREATIVITAS ANAK USIA DINI MELALUI KEGIATAN MEWARNAI - Badriah Rahmawati; Eka Mei Ratnasari; S Suryadi (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2020)
This study aims to improve children's creativity and the quality of learning through coloring activities in TK Pertiwi 1 Lampung. This research is motivated by the obstacles faced in developing children's ideas and imaginations. This type of research is Classroom Action Research. This research was conducted in 2 cycles consisting of 3 times at the meeting of each cycle. The subjects in this study were class B as many as 15 children consisting of 9 girls and 6 boys. Data collection through observation sheets. The results showed that student learning outcomes increased, namely in the first cycle there were 4 children who developed very well (BSB), developed according to expectations (BSH) there were 2 children, began to develop (MB) there were 2 children, not yet developed (BB ) there are 7 children. Whereas in cycle 2 there were 13 children who developed very well (BSB), developed according to expectations (BSH) 1 child, started to develop (MB) 1 child, and had not developed (BB) did not exist. These results illustrate that through coloring activities can increase children's creativity. Keywords: Early Childhood, Creativity, Coloring